Towards the use of drama as a therapeutic tool to enhance emotional rehabilitation for people living with HIV/Aids: a case study of Paradiso HIV/Aids support organisation - Mwalwanda, Basimenye Nabatile (My University, 2010)
ABSTRACT This study explores ways to address the emotional needs of people living with HIV/Aids, with specific focus on Paradiso group therapy in Lilongwe, Malawi. The study recognises that people living with HIV/Aids deal with physical as well as psychological challenges. Based on this premise, this study investigates whether the use of drama and theatre processes can enhance emotional rehabilitation for people living with HIV/Aids, and seeks to explore what drama and theatre methods would contribute towards their emotional health. The study examines Theatre for Development (TFD), a methodology that has played a critical role in addressing various HIV/Aids issues in Malawi. In the assessment, it is argued that TFD remains a relevant model but only as an awareness building strategy about HIV/Aids. This study concludes that TFD is, however, unable to help people explore, confront and express the personal traumatic experiences of living with HIV/Aids. Likewise, the investigation finds the traditional method of teaching utilised by the Paradiso group therapy inadequate in the sense that it does not acknowledge the lived experiences of people living with HIV/Aids. To this end, an integrated process-orientated drama methodology; drawing on the educational elements of process drama and the healing aspects of drama therapy is developed. The methodology was tested in a series of workshops with Paradiso group therapy members. The outcomes reveal that the approach is effective in providing a clear structure through which people can examine the trauma of stigma as a result of living with HIV/Aids. The study further reveals that an integrated process-orientated drama methodology is effective in enabling people to deconstruct negative HIV/Aids beliefs and narratives and in facilitating the reconstruction of new and functional ones that allow them to experience healing and emotional growth.